2018
DOI: 10.22159/ajpcr.2018.v11i9.26661
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin and Interferon-Gamma as Immune Response Markers in Betathalassemia Major Patients

Abstract: Objective: The assessment of neopterin and interferon-gamma (IFN-γ) levels as a part of immune system response about serum iron status in β-thalassemia (TM) major patients.Methods: Spectrophotometry applied for the estimation of iron status including serum iron level, total iron-binding capacity, and unsaturated iron-binding capacity. Enzyme-linked immunosorbent assay (ELISA) applied for the estimation of the serum cytokines included neopterin and IFN-γ also serum ferritin estimation by ELISA from 130 β-TM maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…In contrast to previous finding that indicated higher level of serum Neopterin in βthalassemia patients (Gharagozloo et al, 2009, Obeid et al, 2018, our study showed that there was no significant difference between thalassemia patients and healthy controls. On the other hands, serum Neopterin level was significantly reduced in splenectomized patients when compared to nonsplenoctimsed patients.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous finding that indicated higher level of serum Neopterin in βthalassemia patients (Gharagozloo et al, 2009, Obeid et al, 2018, our study showed that there was no significant difference between thalassemia patients and healthy controls. On the other hands, serum Neopterin level was significantly reduced in splenectomized patients when compared to nonsplenoctimsed patients.…”
Section: Resultscontrasting
confidence: 99%
“…Neopterin has been used in clinical trials to evaluate bacterial and viral infections, autoimmune disorders, and cancer (Hoffmann et al, 2003). Obeid and his colleagues discovered that thalassemia patients had considerably greater serum levels of IFN-γ and Neopterin when compared to healthy controls (Obeid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Aspartic acid present in high concentrations in the synaptic vesicles of axon terminals, depolarization of nerve endings with potassium ions evokes an immediate release of D-Aspartic acid in a Ca 2+ dependent manner, specific receptors for D-Aspartic acid occur at the postsynaptic membrane; and stimulation of nerve endings with D-Asp triggers signal transduction by increasing the second messenger cAMPD, Aspartic acid plays an important role in the initial phases of central nervous system development in vertebrates (ICOSR, 2011, Obeid, Al-A'araji, Matti & Fawzi, 2018. There is a significant increase in the contents of glutamate and aspartate was found beginning with the first 6 hours of the stroke onset and the degree and duration of such elevation correlated with severity of the stroke (Skvortsova et al, 1999) while there is decreased in plasma level of aspartic acid in Parkinson disease (Jimenez-Jimenez et al, 1996).…”
Section: Introductionmentioning
confidence: 99%